Staging heart failure patients with secondary mitral regurgitation undergoing transcatheter edge-to-edge repair. (3rd October 2022) - Stolz, L; Karam, N; Von Bardeleben, R S; Pfister, R; Petronio, A; Butter, C; Melica, B; Praz, F; Massberg, S; Kalbacher, D; Lurz, P; Adamo, M; et al.
Abstract: Background: Heart failure with reduced ejection fraction (HFrEF) and secondary mitral regurgitation (SMR) are closely related. Progression of HFrEF-SMR is associated with characteristic pathophysiological changes. Recently, staging of HFrEF-SMR patients showed prognostic value in a SMR cohort on medical therapy. Whether these stages are prognostic for SMR patients undergoing transcatheter edge-to-edge mitral valve repair (M-TEER) in addition to drug therapy is unknown. Purpose: The present study aimed at classifying HFrEF-SMR patients undergoing M-TEER into progressive disease stages based on cardiac and extracardiac involvement. We sought to evaluate the impact of the disease stages on survival outcome and symptomatic improvement after M-TEER Methods: Based on echocardiographic transthoracic evaluation, patients were assigned into one of the following subsequent HFrEF-SMR stages representing disease progression (Figure 1): left ventricular (LV) dysfunction alone (Stage 1, LV end diastolic volume ≥159 ml and/or LV ejection fraction <50%); left atrial (LA) involvement (Stage 2, history of atrial fibrillation and/or indexed LA volume >34 ml/m 2 ); right ventricular (RV) pressure/volume overload (Stage 3, tricuspid regurgitation ≥3+ and/or systolic pulmonary artery pressure >65 mmHg); biventricular failure (Stage 4, RV to pulmonary artery coupling <0.274 mm/mmHg). A Cox regression model was implemented to investigate the impact of HFrEF-SMR stages on two-year all-cause mortality and symptomatic outcome was assessed with New York Heart Association (NYHA) functional class at follow-up. Results: Among a total of 849 included patients who underwent M-TEER for symptomatic MR from 2008 until 2019, 9.5% (n=81) presented with LV dysfunction alone, 46% (n=393) with LA involvement, 15% (n=129) with pressure/volume overload and 29% (n=246) with biventricular failure. At baseline and follow-up, successive HFrEF-SMR stages were associated with more severe heart failure symptoms as expressed by NYHA functional class. An increase in HFrEF-SMR stage was associated with increased two-year all-cause mortality rates after M-TEER (Hazard ratio 1.39, confidence interval 1.23–1.58, p<0.01, Figure 2). Conclusions: Classifying HFrEF-SMR patients undergoing M-TEER into subsequent disease stages provides prognostic value regarding heart failure symptoms and survival. Funding Acknowledgement: Type of funding sources: None.